2017
DOI: 10.1002/hed.24791
|View full text |Cite
|
Sign up to set email alerts
|

Activation of transforming growth factor‐β1 by thrombin via integrins αvβ1, αvβ3, and αvβ5 in buccal fibroblasts: Suppression by epigallocatechin‐3‐gallate

Abstract: Thrombin induces αvβ1, αvβ3, and αvβ5 integrins-mediated TGF-β1 activations via ROCK signaling. EGCG inhibits thrombin-induced CCN2 synthesis in BMFs by suppressing latent TGF-β1 activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…One study demonstrated that EGCG attenuates fibroblast proliferation and excessive collagen production by interfering with TGF-β1 signaling ( 37 ). EGCG inhibits the expression of tumor necrosis factor receptor associated factor 6, inhibits the activation of TGF-b1 and regulates rheumatoid arthritis ( 38 ). The present study demonstrated that following EGCG treatment, TGF-β1 p-Smad3 expression levels were significantly increased in mouse models of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that EGCG attenuates fibroblast proliferation and excessive collagen production by interfering with TGF-β1 signaling ( 37 ). EGCG inhibits the expression of tumor necrosis factor receptor associated factor 6, inhibits the activation of TGF-b1 and regulates rheumatoid arthritis ( 38 ). The present study demonstrated that following EGCG treatment, TGF-β1 p-Smad3 expression levels were significantly increased in mouse models of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Although TGF-b from activated platelets generally exists in its latent form, activated platelets can convert this to an active form (37) ; thrombin can also activate TGF-b through cell surface integrin. (38) Our data revealed that TGF-b from activated platelet supernatant upregulates TF in MG63 cells, but further TGF-b activation then occurs in the tumor microenvironment. Next, we confirmed that platelets activated by osteosarcoma cells release both total and active TGF-b.…”
Section: Discussionmentioning
confidence: 60%
“…As expected, with thrombin stimulation, both total and active TGF‐β were found in activated platelet supernatant. Although TGF‐β from activated platelets generally exists in its latent form, activated platelets can convert this to an active form; thrombin can also activate TGF‐β through cell surface integrin . Our data revealed that TGF‐β from activated platelet supernatant upregulates TF in MG63 cells, but further TGF‐β activation then occurs in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 72%
“…Current evidence has suggested that TGF-β signaling is the key pathway to trigger the manifestation of OSF [7,8]. It has been shown that thrombin released from microtrauma during areca nut chewing was able to induce αvβ1, αvβ3, and αvβ5 integrins-mediated TGF-β1 activation, leading to production of connective tissue growth factor (CTGF) in human BMFs [26]. Arecoline-induced mitochondrial ROS also plays a pivotal role in the activation of latent TGFβ1 and the subsequent increase of CTGF and early growth response-1 in BMFs [27].…”
Section: Discussionmentioning
confidence: 99%